Development of building heat detection system: an improvement study - Sulaima, Mohamad Fani; Foo, Jia En; Wan Daud, Wan Mohd Bukhari; Jali, Mohd Hafiz; Ahmad Izzuddin, Tarmizi (Ijecse, 2014)
The increment of the numbers for accidents due to building safety system errors has created a serious disaster over the year. Due to that reason, this paper presents the entitled Building Heat Detection System (BHD System)by the objectives to develop the proper circuit in order to secure the detection device during the building fire attack. A BHD system, also known as fire protection system consists of heat sensing and monitoring system. The sensors detect extreme heat in an area or zone; the control unit processes the signals and sets off evacuation alarms to alert building occupants. This study focused on the design and fabrication of the system prototype to demonstrate the operation of a BHD system in case of fire accidents. Hose reel indicator is included to display the exact location in a building to aid in firefighting. On top of that, exit indicators were added to show the available exits should fire breaks out in a building. This study is hoped to help the system engineers to improve and secure their building safety system in the future.